Safe Investment Education and Anti-Fraud Awareness for the Community of Sanankerto Village, Malang Regency - Novy Karmelita Indrawati (⁠International Journal of Asia Pacific Community Service, 2025)
The rapid expansion of financial technology has provided broader access to digital investment platforms, yet it has simultaneously increased the prevalence of fraudulent schemes such as scams, money games, binary options, and illegal robot trading. These practices have significantly impacted communities in Indonesia, including rural areas with limited financial literacy. Sanankerto Village, Malang Regency recognized as a tourism village with active MSMEs and community-based economic activities faces growing exposure to deceptive investment offers delivered through social media and digital channels. This community service program aims to enhance financial literacy and strengthen residents’ capacity to identify, verify, and avoid illegal investment schemes. Employing a Participatory Action Education approach, the program consists of five stages: needs assessment, educational workshops, hands-on training on legality verification using OJK, Bappebti, and SWI platforms, fraud-identification simulations, and evaluation through pre- and post-test assessments. Findings reveal a substantial increase in participants’ understanding of legal investment principles, the ability to independently check institutional licenses, and heightened vigilance toward digital fraud. The program also produced sustainable outputs, including trained village financial literacy volunteers, educational modules, and anti-fraud posters. Overall, this initiative contributes to improving the financial resilience of Sanankerto Village and preventing economic losses associated with illegal investment practices